Exploring an optimal franchise agreement model for the fuel retail industry in South Africa - Sakoane, Motshidisi Mary-Anne (University of the Witwatersrand, Johannesburg, 2024)
This study explores the complex landscape of fuel retail franchise agreements in South Africa, highlighting the multifaceted challenges and strategic imperatives facing both franchisors and franchisees. The research underscores the importance of sustainable partnership models and adaptive business practices amidst a dynamic market environment. Key findings reveal a complex interplay of regulatory frameworks, market dynamics, and consumer trends, which significantly influence fuel retail franchise agreements. The study emphasises the need for franchise agreements that prioritise flexibility, clarity, and adaptability to ensure mutual benefit and long-term viability. The research contributes to understanding the complexities and challenges within the fuel retail industry, providing valuable guidance for stakeholders. It informs strategic decision-making and offers recommendations for improving franchise agreements, ensuring they meet the evolving needs of the market. The study also highlights limitations, including the specificity of the South African context and the dynamic nature of the industry, and suggests areas for future research, such as the impact of emerging technologies and consumer preferences on franchise operations.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Franchise agreement; Fuel retail industry; Optimal model; Franchisee; Franchisor; UCTD; SDG-7: Affordable and clean energy; SDG-8: Decent work and economic growth